Answer:
See answers below
Explanation:
Standard equation of a line is expressed as y = mx+b
m is the slope
b is the y intercept
Given the coordinate points (-2, -4) and B(1, -7)
Slope m = y2-y1/x2-x1
m = -7-(-4)/1-(-2)
m = -7+4/1+2
m = -3/3
m = -1
Get the intercept
Substitute m = -1 and (1, -7) into y = mx+b
-7 = -1(1) + b
-7 = -1 + b
b = -7+1
b = -6
Get thw equation
y = mx+b
y = -x + (-6)
y = -x - 6
Q.3 The equation in point slope form is expressed as y - y0 = m(x-x0)
Given the point (3, 5)
x0 = 3
y0 = 5
Given the equation y = 2x+3
mx = 2x
m = 2
slope = 2
Substitute the slope and the point in the expression
y - 5 = 2(x -3)
y - 5 = 2x - 6
y - 2x = -6 + 5
y - 2x = -1
This gives the required equation
Q.4 The equation in point slope form is expressed as y - y0 = m(x-x0)
Given the point (5, 7)
x0 = 5
y0 = 7
Slope = 3
Substitute the slope and the point in the expression
y - 7 = 3(x -5)
y - 7 = 3x - 15
y - 3x = -15 + 7
y - 3x = -8
This give the required equation